Reliability experiments of sintered silver based interconnections by accelerated isothermal bending tests - Heilmann, Jens; Nikitin, Ivan; Zschenderlein, Uwe; May, Daniel; Pressel, Klaus; Wunderle, Bernhard (Microelectronics and reliability, 2017)
Integration of more functionality and smaller chips into decreasing package volume leads to increasing heat generation. In addition, the use of new compound semiconductors like SiC and GaN require a high thermal conductivity of the interconnect materials. One of the promising solutions is a layer of sintered silver between semiconductor and substrate. The advantages compared to conventional solders are significant. A higher thermal and electrical conductivity in combination with a higher duty temperature due to a higher melting point should enhance the reliability of the package. However, even as the large scale commercial usage of the material has been started by the industry recently, many important details of the mechanical properties and the reliability behavior are still unknown. While the thermal properties could be characterized relatively easy and are quite repeatable and stable, the mechanical properties - important for the reliability - are extremely process-dependent and wide-spreading. The hunt for lowest feasible sintering process parameters - such as temperature, time and especially pressure - even amplify that behavior and led to an impasse in some cases. Also their failure mechanisms, to be identified in lifetime investigations, are yet unknown as well as their stability and predictability. In order to enable prolonged function of these interfaces, thermo-mechanical reliability has to be assured. Within this paper, we show the status of silver sintering and the problems regarding mechanical material characterization found in literature. Additionally, we present a guideline for the mechanical acceleration of reliability experiments by isothermal bending tests. Finally a proof of concept by failure analysis will be presented. •A review of the state of the art of silver sintering is given.•A concept for mechanical acceleration of lifetime-modelling is presented.•Experimental results of mechanical fatigue tests using nano-silver are presented.•Physics of failure analysis indicates, that mechanical acceleration of fatigue tests can be possible for sintered silver.